NR4A Family Genes: A Review of Comprehensive Prognostic and Gene Expression Profile Analysis in Breast Cancer - Yousefi, Hassan; Fong, Jordyn; Alahari, Suresh K. (Frontiers in Oncology, 2022)
This report is to analyze nuclear receptor (NR) subfamily 4A’s potential role to treat those diagnosed with breast cancer. Here we reviewed the current literature on NR4 family members. We also examined the relative gene expression of the NR4A receptor subfamily in the basal, HER2 (human epidermal growth factor receptor 2) positive, luminal A, and luminal B subtypes using data from tumor samples in The Cancer Genome Atlas (TCGA) and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC). These data showed a positive link between NR4A1-NR4A3 expression and increased overall survival and relapse-free survival in breast cancer patients. In addition, we observed that high expression of NR4A1, NR4A2, and NR4A3 led to better survival. Furthermore, NR4A family genes seem to play an important regulatory role in glycolysis and oxidative phosphorylation in breast cancer. The novel prognostic role of the NR4A1–NR4A3 receptors implicate these receptors as important mediators controlling breast cancer metabolic reprograming and its progression The goal of this report is to establish a strong clinical basis for further investigation into the cellular, molecular, and physiology roles of NR4A genes in breast cancer.